1994
DOI: 10.1016/0885-3924(94)90174-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and pattern of symptoms in patients with cancer pain: A prospective evaluation of 1635 cancer patients referred to a pain clinic

Abstract: In a prospective study, the prevalence of 15 physical symptoms and symptom groups was evaluated in 1635 cancer patients referred to a pain clinic. In addition to pain, patients suffered an average of 3.3 symptoms: insomnia (59%), anorexia (48%), constipation (33%), sweating (28%), nausea (27%), dyspnea (24%), dysphagia (20%), neuropsychiatric symptoms (20%), vomiting (20%), urinary symptoms (14%), dyspepsia (11%), paresis (10%), diarrhea (6%), pruritus (6%), and dermatological symptoms (3%). While symptom prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
114
4
12

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(141 citation statements)
references
References 21 publications
11
114
4
12
Order By: Relevance
“…As cancer pain can occur in conjunction with a number of other symptoms, such as depression, anxiety and experiencing fluctuating mood states, pain may underlie those psychological consequences (Grond et al, 1994). This result is at odds with previous reviews, in which the prevalence of cancer pain was reported as being 74% for a similar population group (Teunissen et al, 2007).…”
Section: The Needs Of Patients With Advanced Incurable Cancercontrasting
confidence: 57%
“…As cancer pain can occur in conjunction with a number of other symptoms, such as depression, anxiety and experiencing fluctuating mood states, pain may underlie those psychological consequences (Grond et al, 1994). This result is at odds with previous reviews, in which the prevalence of cancer pain was reported as being 74% for a similar population group (Teunissen et al, 2007).…”
Section: The Needs Of Patients With Advanced Incurable Cancercontrasting
confidence: 57%
“…The literature also confirms our findings that pain is still prevalent in cancer patients and it has been inadequately treated. In a study by Cleeland et al [5], about 42% of the patients with pain did not receive adequate pain medications. The IASP Task Force on cancer pain survey also demonstrated the inadequacy of cancer pain treatment [4].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the widespread recognition of guidelines for the treatment of cancer pain and increase in opioid consumption, a significant number of patients are still experiencing and suffering from cancer pain. Globally, 80% of the cancer population receive inadequate or no pain medication [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…38 In a study done by Ground et al, the prevalence of nausea is 20-30% in all patients with advanced cancer, and this rises to 70% in the last week of life and 20% of all cancer patients develop vomiting. 39 In a study done by Fainsinger et al, nausea and vomiting was highest in advanced gynaecological cancers (42%) and advanced stomach cancer (36%). 40 It was observed that chronic nausea in the advanced cancer setting was often multifactorial.…”
Section: Discussionmentioning
confidence: 99%